Pathogenesis of recent Lassa virus isolates from lineages II and VII in cynomolgus monkeys. Issue 1 (31st December 2022) - Mateo, Mathieu; Hortion, Jimmy; Perthame, Emeline; Picard, Caroline; Reynard, Stéphanie; Journeaux, Alexandra; Germain, Clara; Carnec, Xavier; Baillet, Nicolas; Borges-Cardoso, Virginie; Pietrosemoli, Natalia; Vallve, Audrey; et al.
ABSTRACT: The area of Lassa virus (LASV) circulation is expanding, with the emergence of highly pathogenic new LASV lineages. Benin recently became an endemic country for LASV and has seen the emergence of a new LASV lineage (VII). The first two outbreaks in 2014 and 2016 showed a relatively high mortality rate compared to other outbreaks. We infected cynomolgus monkeys with two strains belonging to lineage II and lineage VII that were isolated from deceased patients during the 2016 outbreak in Benin. The lineage VII strain (L7) caused uniform mortality. Death was associated with uncontrolled viral replication, unbalanced inflammatory responses characterized by increased concentrations of pro- and anti-inflammatory mediators, and the absence of efficient immune responses, resembling the pathogenesis associated with the prototypic Josiah strain in monkeys. The lineage II strain (L2) showed apparently lower virulence than its counterpart, with a prolonged time to death and a lower mortality rate. Prolonged survival was associated with better control of viral replication, a moderate inflammatory response, and efficient T -cell responses. Transcriptomic analyses also highlighted important differences in the immune responses associated with the outcome. Both strains caused strong inflammation in several organs. Notably, meningitis and encephalitis were observed in the cerebral cortex and cerebellum in all monkeys, independently of the outcome. Due to their apparently high pathogenicity, emerging strains from lineage VII should be considered in preclinical vaccine testing. Lineage II would also be beneficial in pathogenesis studies to study the entire spectrum of Lassa fever severity.